Gaining User Satisfaction of KAI-Access: Eâ€Service Quality Dimensions as Antecedent Through Eâ€Trust - Dewi, Andrieta Shintia; Wulandari, Astri; Rahayu, Agus; Hendrayati, Heny (Department of Management, Faculty of Economics and Business, Brawijaya University, 2023)
BUMN (Indonesian State Owned Company) companies participating in the development of the digital industry are PT. KAI (Indonesian Railways Companies). In 2014, PT. KAI launched an official mobile application to make it easier for users to find information about trains. Online shopping has become more popular as the internet and e-commerce continue to expand. In order to sell their wares online and stay ahead of the competition, businesses must provide reliable online services. The purpose of this research was to contribute to the literature by examining the link between e-service quality (efficiency, privacy, reliability, emotional benefits, and customer service), e-satisfaction, and e-trust. In this study using explanatory statistics, with SEM (Structural Equation Modeling) analysis techniques through data processing software SMART PLS 3.2.9. The researcher used a random sample method to collect data from 400 participants. The results of this research corroborate the existence of a positive connection between the two primary concepts of the measuring model under investigation: e-satisfaction and e-trust. E-trust is a prerequisite for e-satisfaction, and an app may make Indonesian customers happy if it provides them reasons to trust it. This study's findings indicate that a consumer's level of post-purchase happiness is significantly impacted by how they perceive their trust to have been treated. An improvement in the quality of e-services will have a positive effect on consumers, who will make more purchases in the future.